Portuguese syntax : new comparative studies - Costa, João, 1972- (Oxford studies in comparative syntax., 2000)
These articles focus on clause structure, clitic placement, word order variation, pronominal system, verb movement, quantification, and distribution of particles. They are written within the ""principles and parameters"" framework and contrast Portuguese with other Romance languages.